PERSEPSI SISWA ADMINISTRASI PERKANTORAN TERHADAP KETRAMPILAN BERKOMUNIKASI DAN KECERDASAN EMOSIONAL GURU DALAM MEMPENGARUHI MOTIVASI BELAJAR - DEWI, MONICA (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2013)
The Purpose of this research is to know : (1) is there any influence on techer communication skill on the student learning motivation (2) is there any  influence on teacher?s emotional intelligent on the student?s learning motivation (3) is there any influence teacher?s comunication skill and emotional intelligent on the student learning motivation. This reasearch is located at SMK Ksristen 1 Surakarta.Appropriate with the problem and purpose of this research, the research uses Non Experiment Correlasion, in Quantitative. Population of this research are 121 students office administration, and Sampel of this research are 97 students. Sampling technic what used in  this research is Proportionate Stratified Random Sampling. Technic data collecting for variable communication skill, emotional intelligent, and Learning Motivation used questionnaire technical. While data analysis technic, researcher used regresi ganda analysis with two dependent variable and one independent variable. Based on the result the research, researcher can conclude : (1) the higher variable teacher?s communication skill will positive influence on the student?s learning motivation, because is bigger than or 0,2064 > 0,202. (2) the higher variable teacher?s emotional intelligent will positive influence on the student?s learning motivation, because is bigger than or 0,2206 > 0,202. (3) the higher teacher?s communication skill and emotional intelligent will positive influence on the student?s learning motivation, because is bigger than or 4,843 > 3,09. Relative Contribution of communication skill is 46,75% and emotional intelligent is 53,25%.. Key word          : communication skill, emotional intelligent, motivation